Multidimensional Poverty Index 2013 : brief methodological note and results - Alkire, S; Conconi, A; Roche, J (Oxford Poverty & Human Development Initiative (OPHI), 2013)
The Multidimensional Poverty Index (MPI) 2013 uses the same parameters (dimensions, indicators, cutoffs and weights) and the same functional form as in previous years. The main innovation this year consists in updating the estimations for a series of countries and providing further possibilities for analysis over time. This brief methodological note outlines specific changes and clarifications concerning the MPI 2013 estimations, and presents the tables with the full results. It first explains the main updates in the MPI 2013 as well as the policies that will govern the MPI updates from 2013. It summarizes the MPI methodology that has been presented in detail in other documents (Alkire and Santos 2010; Alkire, Roche, Santos and Seth 2011). Then it explains the DHS nutritional subsamples and treatment for analysis over time. Finally, brief guidelines on how to undertake accurate analysis of changes over time are presented. The methodologies used to generate the tables on the MPI and the 104 country briefings and interactive maps available on OPHI’s website, as well as the results published in the 2013 Human Development Report, are presented in this note.